2013
DOI: 10.1021/bc300672b
|View full text |Cite
|
Sign up to set email alerts
|

Relative Performance of Alkynes in Copper-Catalyzed Azide–Alkyne Cycloaddition

Abstract: Copper-catalyzed azide–alkyne cycloaddition (CuAAC) has found numerous applications in a variety of fields. We report here only modest differences in the reactivity of various classes of terminal alkynes under typical bioconjugative and preparative organic conditions. Propargyl compounds represent an excellent combination of azide reactivity, ease of installation, and cost. Electronically activated propiolamides are slightly more reactive, at the expense of increased propensity for Michael addition. Certain al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 48 publications
3
63
0
Order By: Relevance
“…Alkynes 3 , 4 , 5 , 6 , and 8 showed a noticeable increase in the average initial polymerization rate, as compared to alkyne 7, during the first 2 minutes of irradiation, mainly due to the higher reactivity of an alkyne functional group next to an ether linkage compared to a hydrocarbon linkage. 32,34 The alkyne reactivity was also confirmed through a study of small molecule model compound reactivity in solution by FTIR, using a 2 M solution in DMF of propargyl alcohol or 5-hexyn-1-ol, difunctional azides 2c , 2% CuCl 2 -[PMDETA], and 4% DMPA, irradiated at ambient temperature (Fig. S1 † ).…”
Section: Resultsmentioning
confidence: 76%
“…Alkynes 3 , 4 , 5 , 6 , and 8 showed a noticeable increase in the average initial polymerization rate, as compared to alkyne 7, during the first 2 minutes of irradiation, mainly due to the higher reactivity of an alkyne functional group next to an ether linkage compared to a hydrocarbon linkage. 32,34 The alkyne reactivity was also confirmed through a study of small molecule model compound reactivity in solution by FTIR, using a 2 M solution in DMF of propargyl alcohol or 5-hexyn-1-ol, difunctional azides 2c , 2% CuCl 2 -[PMDETA], and 4% DMPA, irradiated at ambient temperature (Fig. S1 † ).…”
Section: Resultsmentioning
confidence: 76%
“…48 Further modification of the remaining amino group to generate carbamate bonds yields substrates S1-S4, which contain different alkyne or alkene groups. The carbamate bond of S1 was previously shown to be hydrolyzed in the presence of CuIJI), 51 while the carbamate bond in S2 is labile in the presence of PdIJII) catalysts. 52,53 The hydrolytic stability of the carbamate bonds in S3 and S4 in the presence of CuIJI) is not known.…”
Section: Design and Synthesis Of Fluorogenic Substratesmentioning
confidence: 99%
“…Of the tested Pd catalysts, Allyl 2 Pd 2 Cl 2 and Pd(dba) 2 (Scheme D) showed the highest catalytic activity, unmasking 80 % of a proc‐caged lysine with a catalyst loading of 0.1 equivalence in PBS. A Pd(cod)Cl 2 catalyst was also shown to cleave thioether linkers containing a propargyl carbamate, and Cu I ‐complexes can remove tertiary propargyloxycarbonyl groups from amines …”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
“…A Pd(cod)Cl 2 catalyst was also shown to cleave thioether linkers containing ap ropargyl carbamate, [22] and Cu I -complexes can remove tertiaryp ropargyloxycarbonyl groups from amines. [23] Metallic Pd nanoparticlesc an also remove proc groups. [24] These nanoparticles effectively deprotected proc-protected aminocoumarin, achieving 95 %c onversion within minutes in HEPES/DMSO( 95:5) with stoichiometricP d 0 .M oreover,i tw as demonstrated that Pd 0 resins [25] and ah ybrid magnetic iron and Pd nanowire [26] werea ble to deprotect propargyl groups from 5-fluorouracil.…”
Section: Transition-metal-catalyzeddissociative Reactionsmentioning
confidence: 99%